Christian Hospitality: An Entrance to Christian Pastoral Assistance and Counseling in Times of Crisis - Hiruniko Ruben Siregar; Junifrius Gultom (Bisma The Journal of Counseling, 2022)
The need for pastoral assistance and counseling is increasingly being felt in various sectors of society, both Christian and non-Christian. The economic, social, and political crisis, which resulted in crises in other fields, including health, education, and morals, made a crisis that had a widespread impact in Indonesia. This has triggered the community's need for pastoral care and counseling. This works to help them through an interactive, reciprocal, and in-depth conversation to find the core of the problem and lead to a solution. However, for this interaction to occur, hospitality practices are undoubtedly needed so that the counselee is willing to be involved and open up. The purpose of this study was to examine the concept of hospitality as the first step in the presence of pastoral assistance and counseling in times of crisis for Christians. The research method used is descriptive qualitative. The results showed that Christian hospitality requires counselors to have empathy and openness to counselees while sharpening their ability to carry out congregational counseling. Without it, the congregation will remain in a depressed and stressed existence due to the crisis they are facing.